Recommendations for the safety of hospitalised patients in the context of the COVID-19 pandemic: a scoping review - Daniela Campos de Andrade Lourenção; Maristela Santini Martins; Rafael Rodrigo da Silva Pimentel; Janine Melo de Oliveira; Letícia Tuany de Carvalho Nogueira Manganoti; Roberto Chrispim Modesto; Maiquele Sirlei dos Santos Silva; Marcelo José dos Santos (BMJ Open, 2022)
Objective To map the recommendations for hospitalised patient safety in the context of the COVID-19 pandemic.Design Scoping review using the method recommended by the Joanna Briggs Institute.Data sources Databases: Medline, SCOPUS, EMBASE, ScienceDirect, LILACS, CINAHL and IBECS; grey literature platform: Google Scholar; and 11 official websites of leading healthcare institutions were searched on 27 April 2021 and updated on 11 April 2022.Eligibility criteria We included documents that present recommendations for the safety of hospitalised patients in the context of the COVID-19 pandemic, published in any language, from 2020 onwards.Data extraction and synthesis Data extraction was performed in pairs with consensus rounds. A descriptive analysis was carried out to present the main characteristics of the articles. Qualitative data from the extraction of recommendations were analysed through content analysis.Results One hundred and twenty-five documents were included. Most papers were identified as expert consensus (n=56, 44.8%). Forty-six recommendations were identified for the safety of hospitalised patients: 17 relating to the reorganisation of health services related to the flow of patients, the management of human and material resources and the reorganisation of the hospital environment; 11 on the approach to the airways and the prevention of the spread of aerosols; 11 related to sanitary and hygiene issues; 4 about proper use of personal protective equipment and 3 for effective communication.Conclusions The recommendations mapped in this scoping review present the best practices produced so far and serve as a basis for planning and implementing good practices to ensure safe hospital care, during and after COVID-19. The engagement of everyone involved in the care of hospitalised patients is essential to consolidate the mapped recommendations and provide dignified, safe and quality care.